Thrombin Physiology and Disease - Maragoudakis, Michael E.; Tsopanoglou, Nikos E.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2009)
It has become increasingly evident in recent years that, apart from the key role that thrombin plays in the blood coagulation cascade, thrombin also elicits cellular actions via the activation of proteinase-activated receptors, which are present in many cell types. These effects of thrombin are seen in a variety of physiological as well as pathological phenomena, including vascular development and physiology, tumor progression and metastasis, neuronal functions, inflammation, angiogenesis. Thrombin: Physiology and Disease, edited by Michael E. Maragoudakis and Nikos E. Tsopanoglou, emphasizes the new developments in this important field of research and provides the basis for translating these findings into therapeutic targets.".
Thrombin: Structure, Functions, and Regulation -- Thrombin: To PAR or Not to PAR, and the Regulation of Inflammation -- Regulation of Thrombin Receptor Signaling -- Thrombin-Activated Protein C: Integrated to Regulate Vascular Physiology -- The Role of Thrombin in Vascular Development -- The Role of Thrombin in Angiogenesis -- Thrombin and Thrombin Peptides in Wound Healing and Tissue Repair -- The Role of Thrombin and Thrombin Receptors in the Brain -- The Role of Thrombin in Tumor Biology -- The Role of Thrombin and its Receptors in Epithelial Malignancies: Lessons from a Transgenic Mouse Model and Transcriptional Regulation -- Anti-thrombotic Therapy in Cancer Patients -- Thrombin Receptor Modulators: Medicinal Chemistry, Biological Evaluation, and Clinical Application -- Novel Anticoagulant Therapy: Principle and Practice.
Keywords: Medicine; Cancer research; Human physiology; Pharmacology; Epidemiology; Biochemistry; Biomedicine; Human Physiology; Cancer Research; Pharmacology/Toxicology.; Biochemistry, general; Epidemiology; Electronic books